Effective Haskell : solving real-world problems with strongly typed functional programming - Skinner, Rebecca (Web developer) (Pragmatic programmers., 2022)
Put the power of Haskell to work in your programs, learning from an engineer who uses Haskell daily to get practical work done efficiently. Leverage powerful features like Monad Transformers and Type Families to build useful applications. Realize the benefits of a pure functional language, like protecting your code from side effects. Manage concurrent processes fearlessly. Apply functional techniques to working with databases and building RESTful services. Don't get bogged down in theory, but learn to employ advanced programming concepts to solve real-world problems. Don't just learn the syntax, but dive deeply into Haskell as you build efficient, well-tested programs. Haskell is a pure functional programming language with a rich ecosystem of tools and libraries. Designed to push the boundaries of programming, it offers unparalleled power for building reliable and maintainable systems. But to unleash that power, you need a guide. Effective Haskell is that guide. Written by an engineer who understands how to apply Haskell to the real world and uses it daily to get practical work done, it is your ticket to Haskell mastery. Gain deep understanding of how Haskell deals with IO and the outside world by writing a complete Haskell application that does several different kinds of IO. Reinforce your learnings with practice exercises in every chapter. Write stable and performant code using Haskell's type system, code that is easier to grow and refactor. Leverage the power of pure functional programming to improve collaboration, make concurrency safe and easy, and make large code bases manageable. Implement type-safe web services, write generative tests, design strongly typed embedded domain-specific languages, and build applications that exploit parallelism and concurrency without fear of deadlocks and race conditions. Create and deploy cloud-native Haskell applications. Master the performance characteristics of functional applications to make them run faster and use less memory. Write Haskell programs that solve real-world business problems.